2004
DOI: 10.1038/sj.jea.7500305
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of lifetime accumulated ELF-EMF exposure from household appliances in the context of a retrospective epidemiological case–control study

Abstract: In Europe household appliances are a major source of indoor 50 Hz magnetic field exposure. A number of epidemiological studies have reported associations between leukemia risk and personal use of household appliances. In the ''Norddeutsche Leuka¨mie und Lymphomstudie'' (NLL), which was conducted in Northern Germany (Schleswig-Holstein and Lower Saxony) between 1997 and 2001, lifetime use of a preselected array of electric appliances (microwave ovens, hair-dryers, motorized electrical alarm clocks (i.e. that us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
(39 reference statements)
0
18
2
Order By: Relevance
“…Other studies that we have conducted in the past demonstrated that exposure to certain domestic electrical appliances can cause EMF exposure that may well exceed the average exposure levels of workers in electrical trades 33. However, in the USA no strong correlation between occupational and residential exposure to EMF has been noted 25.…”
Section: Discussionmentioning
confidence: 78%
“…Other studies that we have conducted in the past demonstrated that exposure to certain domestic electrical appliances can cause EMF exposure that may well exceed the average exposure levels of workers in electrical trades 33. However, in the USA no strong correlation between occupational and residential exposure to EMF has been noted 25.…”
Section: Discussionmentioning
confidence: 78%
“…The results of questionnaires about children’s house appliances showed that TVs watching and the use of fixed-line telephone were statistically significant between school A and school B. But the EMF generated from TVs and fixed-line telephone was weak and mostly less than 0.1 µT [62].…”
Section: Discussionmentioning
confidence: 98%
“…An interesting, albeit diYcult, factor to investigate in workplace epidemiological studies would be non-occupational household exposure to EMFs. Behrens et al (2004) looked at long term cumulative exposures to EMFs, and found that power-line workers would be exposed to 6,250 T h for 10 years of employment compared to 21,608 T h for 10 years of exposure from sleeping beside an electric clock (Behrens et al 2004). This type of household exposure should be taken into account in future population based studies.…”
Section: Discussionmentioning
confidence: 97%